Efectos de un programa educativo Zeka para el mejoramiento de la comprensión lectora en estudiantes de tercer grado de educación secundaria de la Institución Educativa Tnte. Manuel Clavero Muga, Iquitos 2022 - Franco Davila, Zandy Fiorella (2024)
The general objective of this research was to evaluate the effect of the Zeka educational program on the improvement of reading comprehension in third-grade secondary school students of the Tnte Manuel Clavero Muga educational institution, Iquitos 2022. The type and design of the research was experimental and quasiexperimental respectively. The population was 132 students, with a sample of 67 students divided into two groups. The experimental group with 34 students and the control group with 33 students, a pre-test and a posttest were applied to both groups. The data collection instrument was a reading comprehension questionnaire, which was valid through expert judgment, obtaining a score of 92 and a reliability of 80,2%, relevant for its application. The descriptive statistical analysis indicates that after the application of the educational program, a considerable reduction was obtained in the defend level with 2 (6%) students, the same as in the process level with 5 (15%) students, while an increase considerable in the satisfactory level 10 (29%) students, the same as in the outstanding level 17 (50%). Contrasting hypotheses using the Wilcoxon test statistic for related samples, which determined that the effect of the educational program was significant in improving reading comprehension, with a p-value = 0,000 < 0,05.